THE CONTEMPORARY SIGNIFICANCE OF ABU RAYHAN BERUNI'S SCIENTIFIC DISCOVERIES - Nilufar Niyozova (Western European Studies, 2023)
This article describes the development of modern science, the creative heritage of great scientists who made a significant contribution to it. In particular, the essence of Abu Rayhan Beruni's works, the relevance of his study today, and his invaluable contribution to world science are described. Some aspects of the greatest works of art are also touched upon.
Keywords: Science; development; scholars